2021
DOI: 10.52054/fvvo.13.4.039
|View full text |Cite
|
Sign up to set email alerts
|

Short stay laparoscopic hysterectomy: An evaluation of feasibility and patient satisfaction

Abstract: Background: Short-stay total laparoscopic hysterectomy (TLH) could lead to reduced hospital costs and decrease complications associated with hospitalisation such as hospital acquired-infection and venous thromboembolism. Objective: To evaluate the feasibility, safety and patient satisfaction of a novel short ‘less than 23-hour’ stay TLH protocol. Material and Methods: Prospective cohort study, at Birmingham Women’s Hospital, United Kingdom including eligible women undergoing TLH for benign indications or ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Similarly with previous reports, the multivariate logistic regression analysis of the present study revealed that a history of pelvic surgery and adenomyosis significantly increased the probability of difficult surgery 30 . Previous studies suggested that pelvic adhesions were significant risk factors for surgical complications and conversion to laparotomy.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly with previous reports, the multivariate logistic regression analysis of the present study revealed that a history of pelvic surgery and adenomyosis significantly increased the probability of difficult surgery 30 . Previous studies suggested that pelvic adhesions were significant risk factors for surgical complications and conversion to laparotomy.…”
Section: Discussionsupporting
confidence: 90%
“…The Diamond trial, which was designed to compare surgery for deep endometriosis with medical treatment, was closed by its funders (w3.abdn.ac.uk/hsru/DIAMOND/Public/Public/index.cshtml). Similarly, the closure of the LAVA trial for the same reason as explained by Antoun et al (2024) in this issue of Facts, Views and Vision may be a sign that the glass ceiling is becoming multi-layered.…”
Section: The Glass Ceiling For Endometriosis Surgery-oriented Gynaeco...mentioning
confidence: 81%
“…Antoun et al reported positive results for SDD following hysterectomies. Overall, 81% of the outpatient protocol group were discharged successfully and factors delaying discharge were more complex surgery, urinary retention, vaginal bleeding and abdominal pain [19]. Wield et al published a retrospective cohort study, including 1124 patients undergoing minimal invasive hysterectomy.…”
Section: Experience In More Extensive Surgeriesmentioning
confidence: 99%